The short term residential college: a model for the future - Herrick, John (2011)
This study explores a common perception that the number of short term adult residential colleges in England and Wales is in decline due to a lack of clarity of purpose, little or no investment and an apparent lack of strategic direction on the part of those who own these establishments. This is despite clear evidence that studying in a residential setting enhances the quality of the learning experience. In very practical terms this research will explore what kind of business model might be successful in such circumstances, and provide an opportunity to secure the future of these unique establishments. The thesis examines the value of such institutions and goes on to investigate the possible reasons why, over the past 60 years the number of short term residential colleges has declined. By examining the financial and enrolment results of five colleges over a two year period, as well as interviewing principals and learners, proposes a model to secure a future for residential education in this country. The topic for this thesis was identified by the author as a result of 20 years experience as Principal of a short term residential college and latterly Head of a county residential education service. The colleges investigated were situated in England and differed in size, ownership and managerial structure. They have over the past 50 – 60 years promoted and sold adult residential courses of varying lengths to the adult population. The research approach adopted in this thesis includes an examination of available literature to determine the original purpose and subsequent development of short term residential colleges. Two major research strategies were used: firstly quantitative analysis of data collected over a two year period representing five different approaches to ownership and management and secondly qualitative analysis of data collected from interviews with principals and active learners to establish the present and future position direction of the five case studies. The data was triangulated to demonstrate concurrent validity, reliability and confidence in the findings. The findings of this research provide evidence that there has, over the past 60 years, been a decline in the number of short term residential colleges and that the decline is mainly confined to those colleges owned and managed by county councils. Of the five case studies, three owned by county (or city) councils face an uncertain future due to lack of direction, commitment and investment as well as financial constraints placed upon them. The findings established that active learners clearly supported the quality of residential learning experience. This thesis recommends that to survive colleges must have a clear unambiguous purpose fit for the 21st century. Colleges that are not charitable organisations would benefit from adopting the organisation model in having clear objects encapsulating a unique selling point whether it is defined as a segment of the adult learning sector or a specialist subject area. The main conclusions drawn from this study are that the adult residential college has a place in the adult learning landscape. Colleges must be financially independent and be nationally recognised for outstanding quality in the adult residential courses they offer.